Cambios quimicos ocasionados por encalamiento y uso de lombrinaza en la etapa de almacigo del cafe - Diaz M, C.=700 1 Sadeghian K, S.; Morales L, C.S.
(Es, En)
Ilus., 32 ref.
Keywords: SUELO; ACIDEZ; PH DEL SUELO; ENMIENDAS DEL SUELO; CAL AGRICOLA; ESCORIAS; MAGNESIO; FOSFORO; COLOMBIA